AFD PENGARUH PRESTASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. JASA MARGA MEDAN - NANDA, ANANDA FITRIANI DEEWI (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
The purpose of this study was to determine the effect of work performance on employee job satisfaction at PT. Jasa Marga Medan. The population in this study were all employees of PT. Jasa Marga Medan, a total of 32 people, and 32 people will be tested. The selection in this study uses the selection method with the Slovin formula. Data collection method with a questionnaire. Validity and reliability were then tested. The data analysis technique used is multiple linear regression. The results showed that there was a significant effect of work performance on employee job satisfaction at PT. Jasa Marga Medan.